Association of serum creatinine-to-albumin ratio with 28-day all-cause mortality in older adults critically ill patients with sepsis: a retrospective analysis of the MIMIC-IV database - Lixin Zhao; Haixia Chai; Sifang Yu; Fang Chen; Caiyun Zhang; Yancun Liu; Yanfen Chai (BMC Geriatrics)
Abstract Background Sepsis has posed a significant global public health challenge, with advanced age, chronic diseases, and medication history in the older adults population significantly increasing the risk of organ failure or death. Serum creatinine (Cr) and albumin (Alb) are important predictors of mortality in individuals with various diseases. Therefore, our research aimed to evaluate the relationship between serum creatinine to albumin ratio (CAR) and 28-day all-cause mortality in older adults patients with sepsis. Methods Using the Medical Information Mart for Intensive Care IV (MIMIC-IV) database, we identified older adults patients with sepsis and applied Kaplan-Meier (K-M) curves and multivariable logistic regression to evaluate the association between CAR and 28-day all-cause mortality. Restricted cubic spline (RCS) analysis explored the nonlinear relationship, and subgroup analyses were conducted. Results After applying inclusion and exclusion criteria, a total of 2,350 older adults patients with sepsis were enrolled, among whom the proportion of non-survivors was 34.89%. Survivors had longer hospital stays and lower CAR. Patients in the highest CAR quartile (Q4) exhibited significantly higher levels of creatinine, and various disease scores. Additionally, the 28-day all-cause mortality in the ICU for the Q4 group was significantly higher than in the other groups (p < 0.0001). After adjusting for confounding factors, the 28-day ICU all-cause mortality was still significantly increased, with a nonlinear relationship (P < 0.001). This association was further confirmed in subgroup analyses, where the predictive value of CAR for 28-day all-cause mortality in the ICU remained consistent across subgroups stratified by comorbidities and individual patient characteristics. Conclusions The MIMIC-IV database revealed a positive association between serum CAR and short-term all-cause mortality in older adults patients with sepsis, with a nonlinear relationship. This research enhances our understanding of the association between serum-based biomarkers and prognosis in older adults patients with sepsis.